FIELD EXPERIENCE REPORT: VIA CHRISTI HOSPITAL - Thompson, Nicholse S. (My University, 2016)
In partial fulfillment of the Master of Public Health (MPH) degree, I completed 180 hours with Via Christi Hospital in Manhattan Kansas for my field experience. Via Christi is a not-for-profit acute care center, serving Manhattan and surrounding areas (Riley County). The organization was created in 1996 by combining Saint Mary and Memorial hospitals to form Mercy Regional Health Center. In 2015, Mercy became Via Christi Hospital. Via Christi is a member of the largest Catholic/nonprofit healthcare system in the country, Ascension. The mission of Via Christi is to serve as a healing presence with special concern for those that are vulnerable. For my experience, I worked with Chris McClead, the Senior Director of Mission Integration, as my mentor. Chris has a Master of Arts in Servant Leadership, as well as a Master of Arts in Theology. Chris’s responsibilities at Via Christi are numerous, but include being the champion of the community benefit program for both Riley and Pottawatomie counties. Part of this role is to serve the needs of the poor and vulnerable by connecting organizations together, towards the result community benefit. He also sits on the board of trustees for the Flint Hills Community clinic, and the board of trustees for Salina Regional Health Center. He also participates in the Riley County Public Health Advisory Council, and is a member of the Flint Hills Wellness Coalition. At the time that I was beginning my field experience, Chris had just started up a new project focusing on family nutrition. This seemed like a great opportunity to get exposure to public health in action.
Keywords: Riley County Kansas